Web based information model : electronic maintenance outline system (e-MOST) as a tool to support maintenance and operations management at Pejabat Pembangunan dan Pengurusan Harta, Kolej Universiti Kejuruteraan dan Teknologi Malaysia - Nasly, Mohamed Ali; Zakaria, Zahrizan (2006)
The purpose of this study was to develop suitable information model called electronic Maintenance Online System (eMOST) to support maintenance and operations at Pejabat Pembangunan dan Pengurusan Harta (PPPH), Kolej Universiti Kejuruteraan dan Teknologi Malaysia (KUKTEM), and to gauge the effectiveness of the proposed information model. Cold Fusion Markup Language was used to develop the purposed information model. Facilities management (FM) is a broad range of functions such as space management, facilities planning and operational management, because of its nature, gathering information is very important to acquire the accurate information. To gain this information, therefore, quantitative studies had been used to achieve the objective of this research. The quantitative part involved data collecting using three different set of questionnaires which is designed with its own purposes. The first set of questionnaire tackle the issues of maintenance management at higher institutions in Malaysia and found that none of them was using any FM software or Computerized Maintenance Management System (CMMS) to assist their maintenance activities and majority of them using out sourcing to carry out their maintenance activities and the most prominent problem faced by the department of maintenance is the delay on procurement process to select maintenance contractor. The second set of questionnaire is to investigate the customer satisfaction index on the performance of maintenance activities done by PPPH, KUKTEM, and found that the most prominent factor which is not satisfy the customers is the response time taken by PPPH. The third set of questionnaire is to evaluate the proposed information model from users' perspective and perceptions, and found that eMOST have a potential to expedite the response time taken by PPPH. Average Index method has been used to analyze the data to rank the factors which is the content in the three set of questionnaires. From the visit and data gather from the three set of questionnaires , found that, maintenance management is a complex function, which is incorporated with many activities and tasks to fulfill its specific objectives, therefore a working procedure or the framework has been developed as a reference to the practice of maintenance management.